2019
DOI: 10.1002/smll.201901020
|View full text |Cite
|
Sign up to set email alerts
|

Designing Highly Efficient and Long‐Term Durable Electrocatalyst for Oxygen Evolution by Coupling B and P into Amorphous Porous NiFe‐Based Material

Abstract: Oxygen evolution reaction (OER) is of great significance for hydrogen production via water electrolysis, which, however, demands development of highly active, durable, and cost‐effective electrocatalysts in order to stride into a renewable energy era. Herein, highly efficient and long‐term durable OER by coupling B and P into an amorphous porous NiFe‐based electrocatalyst is reported, which possesses an amorphous porous metallic bulk structure and high corrosion resistance, and overcomes the issues associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Peng and co‐workers [ 159 ] further reported the highly efficient and long‐term durable OER electrocatalyst via coupling B and P into an amorphous NiFe‐based bulk. The unique NiFeO x H y (shell)/NiFePB (core) configuration ( Figure a–e) significantly increases the activity by using the coupling of P and B atoms that can regulate the electronic structures of the active sites and the conductivity of materials (Figure 20f–h).…”
Section: The Exceptionally Advantaged Nature Of Amorphous Catalysts Tmentioning
confidence: 99%
“…Peng and co‐workers [ 159 ] further reported the highly efficient and long‐term durable OER electrocatalyst via coupling B and P into an amorphous NiFe‐based bulk. The unique NiFeO x H y (shell)/NiFePB (core) configuration ( Figure a–e) significantly increases the activity by using the coupling of P and B atoms that can regulate the electronic structures of the active sites and the conductivity of materials (Figure 20f–h).…”
Section: The Exceptionally Advantaged Nature Of Amorphous Catalysts Tmentioning
confidence: 99%
“…Increasing levels of attention have also been directed to amorphous catalysts, which tend to possess a number of uncoordinated metal atoms with greater numbers of exposed active sites on their surfaces. [179] For example, Peng and co-workers reported a highly efficient and durable OER catalyst by codoping B and P into an amorphous porous NiFe-based electrocatalyst (a-NiFePB), which exhibited an amorphous porous metallic bulk structure and a high corrosion resistance. [179] DFT calculations indicated that P and B codoping delocalized both Fe and Ni at the Fermi energy level and resulted in enhanced p-d hybridization.…”
Section: The Nife Alloys and The Nife-based Nonoxide Familymentioning
confidence: 99%
“…[179] For example, Peng and co-workers reported a highly efficient and durable OER catalyst by codoping B and P into an amorphous porous NiFe-based electrocatalyst (a-NiFePB), which exhibited an amorphous porous metallic bulk structure and a high corrosion resistance. [179] DFT calculations indicated that P and B codoping delocalized both Fe and Ni at the Fermi energy level and resulted in enhanced p-d hybridization. The modified electronic structure and unique porous framework of a-NiFePB therefore contributed to its excellent OER performance, which required a low overpotential of 197 mV to achieve a current density of 10 mA cm −2 , and 233 mV for 100 mA cm −2 , with a small Tafel slope of 34 mV dec −1 .…”
Section: The Nife Alloys and The Nife-based Nonoxide Familymentioning
confidence: 99%
“…Recently, amorphization of either the outer surfaces or the whole catalysts can reasonably destroy the periodicity of the crystal structure and alter the electron distribution of the amorphous zone. [149][150][151][152] In this way, the activity of the electrocatalyst can drastically increase. Amorphization has been demonstrated to be an effective alternative to optimize electrocatalysts.…”
Section: Amorphizationmentioning
confidence: 99%